2011
DOI: 10.1039/c0cc03915b
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging of carbon nanotubes spontaneously filled with solvent

Abstract: For the first time, cryo-TEM imaging is used to directly show spontaneous filling of carbon nanotubes immersed in a solvent in the native state at ambient conditions. Multi-walled carbon nanotubes are dissolved in chlorosulfonic acid, and the high contrast between the acid and the carbon shows the difference between filled and unfilled nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
(43 reference statements)
2
17
0
Order By: Relevance
“…By adjusting the electron dose to the thickness of the vitrified acid cryo‐specimens (thicker areas require more etching), one can generate sufficient contrast to image carbon nanotubes and graphene in superacids (Davis et al ., ; Behabtu et al ., ; Parra‐Vasquez et al ., ; Green et al ., ; Behabtu, ) We have used irradiation contrast enhancement in the development of a method for measuring the length of individual CNTs (Bengio et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…By adjusting the electron dose to the thickness of the vitrified acid cryo‐specimens (thicker areas require more etching), one can generate sufficient contrast to image carbon nanotubes and graphene in superacids (Davis et al ., ; Behabtu et al ., ; Parra‐Vasquez et al ., ; Green et al ., ; Behabtu, ) We have used irradiation contrast enhancement in the development of a method for measuring the length of individual CNTs (Bengio et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Thus, the vitrified acid matrix is more optically dense than the CNTs or graphene embedded in it and appears darker than the dispersed objects. However, the relatively large thickness of the vitrified acid matrix in comparison to nanometre‐scale thickness of the embedded aggregates (especially SWNTs), together with the spontaneous filling of nanotubes by the acid (Green et al ., ), reduces the contrast dramatically. We have found that controlling the cryo‐specimen and imaging parameters, such as film thickness, electron exposure and underfocus, are critical for good contrast.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 A very recent experimental result showed a similar deformation of CNTs lled with chlorosulfonic acid by employing cryogenic transmission electron microscopy. 24 Our previous work has shown that a CNT lled with droplets could be continuously deformed by increasing the lling ratio. 22 The tube was observed to smoothly change from a circular shape to an elliptical shape when the capillary forces outweigh the elastic force.…”
Section: Introductionmentioning
confidence: 98%
“…21 Hence, the phenomenon of elasto-capillarity could not be ignored in liquid inltrated CNTs. The deformation of CNTs has been both theoretically 22 and experimentally 23,24 reported by several research groups. Rossi et al reported elastic deformation of CNTs induced by water condensation on the inner walls of the nanotubes.…”
Section: Introductionmentioning
confidence: 99%